Functional characterization of cutinase genes NsCut1-NsCut4 in Neostagonosporella sichuanensis and their effects on fishscale bamboo - Lu, Mengyao; Liang, Fang; Liu, Lijuan; Yin, Yanji; Xu, Dongxin; Zou, Huan; Liu, Yinggao; Yang, Chunlin (Frontiers in Plant Science, 2025)
Fishscale bamboo rhombic-spot, caused by Neostagonosporella sichuanensis, poses a significant threat to Phyllostachys heteroclada in Sichuan province. Based on genomic analysis, four cutinase genes, NsCut1–NsCut4, were identified, cloned, and functionally validated. Bioinformatics analyses revealed that the proteins encoded by these genes possess secretory functions, lack transmembrane domains, and contain conserved cutinase domains highly homologous to those in other fungi. Recombinant proteins expressed via a prokaryotic system exhibited strong hydrolytic activity against glycerol tributyrate and bamboo white cream at 40°C and pH 8.0, while signal peptide and subcellular localization analyses confirmed their secretory function and localization to the cell wall. Gene knockout experiments were performed to construct deletion strains ΔNsCut and corresponding complemented strains ΔNsCut+. Notably, ΔNsCut1 and ΔNsCut3 resulted in reduced pigmentation, decreased spore production, and increased sensitivity to NaCl, H2O2, and Congo red, along with reduced pathogenicity—indicating that these genes play key roles in metabolic and reproductive processes, oxidative stress responses, and the maintenance of cell wall integrity. In contrast, ΔNsCut2 and ΔNsCut4 did not exhibit significant differences compared to the wild type. This work advances our understanding of the role of cutinases in the pathogenic interaction between N. sichuanensis and P. heteroclada, providing a theoretical basis for further exploration of the pathogen’s underlying mechanisms.